2017
DOI: 10.1128/jvi.02425-16
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Potency and Incomplete Neutralization of Broadly Neutralizing Antibodies against Cell-to-Cell Transmission of HIV-1 with Transmitted Founder Envs

Abstract: Broadly neutralizing antibodies (bNAbs) have been isolated from HIV-1 patients and can potently block infection of a wide spectrum of HIV-1 subtypes. These antibodies define common epitopes shared by many viral isolates. While bNAbs potently antagonize infection with cell-free virus, inhibition of HIV-1 transmission from infected to uninfected CD4 ϩ T cells through virological synapses (VS) has been found to require greater amounts of antibody. In this study, we examined two well-studied molecular clones and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 70 publications
7
70
0
Order By: Relevance
“…For pseudotyping, cells are infected with cell-free, replication-defective virus, which is easily neutralized by bNAbs. In the case of replication-competent virus, however, cells are also infected via cell-to-cell transmission, which is both highly efficient and more difficult for bNAbs to neutralize (23). The mutations most resistant to BMS-626529, i.e., M426L, S375M, and S375M/M434I, were introduced into Env sequence of HIV-1 NL43-ΔR1 , which has a frameshift in vpr, rendering that gene nonfunctional.…”
Section: Importancementioning
confidence: 99%
“…For pseudotyping, cells are infected with cell-free, replication-defective virus, which is easily neutralized by bNAbs. In the case of replication-competent virus, however, cells are also infected via cell-to-cell transmission, which is both highly efficient and more difficult for bNAbs to neutralize (23). The mutations most resistant to BMS-626529, i.e., M426L, S375M, and S375M/M434I, were introduced into Env sequence of HIV-1 NL43-ΔR1 , which has a frameshift in vpr, rendering that gene nonfunctional.…”
Section: Importancementioning
confidence: 99%
“…Recent studies have suggested that the capacity of bNAbs in cell-to-cell transmission varies depending on their mode of action and virus strains [10,53]. A range of bNAbs and virus tests revealed decreased inhibitory activity against HIV-1 cell-to-cell transmission compared with cell-free transmission, and potent capacity in neutralizing free virus spread cannot predict equally relevant for inhibiting cell-to-cell transmission [53,54]. More recently, Parsons examined the efficacy of bNAbs PGT121 against cellassociated SHIV infection and reported partial prevention of infection after cell-associated viral challenge [55].…”
Section: Suboptimal Efficacy In Virus Cell-to-cell Transmissionmentioning
confidence: 99%
“…Notably, the full-length heavy chain-reconstituted VHH (J3-Fc) effectively neutralizes cell-to-cell spread, suggesting that small size is not the only determinant of potency and that other factors are worthy of further exploration [77]. Additionally, due to the higher multiplicity of infection (MOI) during cell-tocell transmission, maintaining high concentrations of bNAbs is crucial for protecting against cell-associated viruses [54]. Alternatively, mAbs that target CD4 or coreceptors competitively or uncompetitively bind to CD4/CCR5 with higher affinity than to HIV glycoprotein 120 (gp120) and might inhibit viral entry as well as cell-to-cell spread [78][79][80].…”
Section: Evaluating Cell-to-cell Transmissionmentioning
confidence: 99%
“…For example, HIV‐1 transmitted cell to cell requires greater concentrations of broadly neutralising antibodies to neutralise virus when compared with cell‐free virus. In a recent study, several broadly neutralising antibodies were found to have a decreased capacity to neutralise virus isolated from HIV‐1 patients in a transfer assay compared with cell‐free virus (Li, Zony, Chen, & Chen, ). Moreover, even though virus transferred via VS is still susceptible to antiretroviral treatment, it is thought to be less sensitive to some commonly used antiretrovirals than cell‐free virus (Sigal et al, ).…”
Section: Virological Synapsementioning
confidence: 99%